ЄМНІСНИЙ ПЕРЕТВОРЮВАЧ ЗУСИЛЬ У СТЯЖНИХ ПРИЗМАХ ОСЕРДЯ СТАТОРА ТУРБОГЕНЕРАТОРА З КОМПЕНСАЦІЄЮ ПОХИБКИ ВІД ПЕРЕКОСУ - Левицький, А.С.; Новік, А.І.; Зайцев, Є.О. (Інститут електродинаміки Національної академії наук України, 2017)
This paper present the method of considerable reduction of measuring error of efforts in the turbogenerator tightening prisms with the use of resilient element and capacity sensor with variable gap is considered. The error, which was as result of arising up from out-of-parallelism of flat sensor circular electrodes, is analyzed. Correlations of sizes external and internal electrodes at that basic constituent of error of transformation "microdisplacement – reciprocal of electric capacity" transforms into an infinitesimal are found. The ratio of size of the external and internal ring electrodes at that basic constituent of error of transformation "microdisplacement – reciprocal of electric capacity "transforms into an infinitesimal are found. The use of concept "Coefficient of defect" for simplification of determination and size estimation out-of-parallelism of electrodes regardless of their geometrical sizes is proposed. Efficiency of the proposed method of correction depending on the coefficient of circular electrodes defect is analysed. It is shown that the relative error of measuring at the large angles of defect diminishes in several times, and at small - in several hundred one times. Refences 7, figure, table.